Voices of Freedom: Dialogue, Plurality, and the Shape of Democracy - Pelengkahu, Muhamad (Jurnal Politik, 2024)
Creating Democracy: Arendt and Bakhtin in Dialogue is an important contribution to political theory and social philosophy. By connecting Hannah Arendt's and Mikhail Bakhtin's thoughts, Hersch offers an innovative perspective on understanding democracy as a dynamic and participatory process. Although coming from different disciplinary backgrounds, Arendt and Bakhtin share fundamental ideas about the importance of freedom, social interaction, and meaning-making in political life.